Effect of Quercetin-Doped Hydrogen Peroxide Gels on Enamel Properties: An In Vitro Study - Alves, Renata de Oliveira [UNESP]; Nunes, Gabriel Pereira [UNESP]; Martins, Tamires Passadori [UNESP]; Alves de Toledo, Priscila Toninatto [UNESP]; Ragghianti, Matheus Henrique Faccioli [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (MDPI, 2025)
This in vitro study evaluated the effects of incorporating quercetin (QC) at varying concentrations (0.25%, 0.5%, and 1%) into a 35% hydrogen peroxide (H2O2) bleaching gel on esthetic outcomes, enamel hardness and roughness, and H2O2 transamelodentinal diffusion. Bovine enamel/dentin discs (n = 180; 12/per group for each analysis) were allocated into five groups: (1) negative control (NC), (2) 35% H2O2 (HP), (3) HP + 0.25% QC, (4) HP + 0.5% QC, and (5) HP + 1% QC. Treatments were applied for 40 min per session across three sessions with 7-day intervals. Color changes were evaluated using the CIELab* color system (ΔEab), with further analysis performed using the CIEDE2000 formula (ΔE00) and the whitening index (ΔWID). Enamel surface hardness, roughness, cross-sectional hardness, and H2O2 diffusion were also evaluated. Data were analyzed using ANOVA, followed by the Student-Newman-Keuls test, with statistical significance set at p < 0.05. All experimental gels resulted in significant color changes (p < 0.001), with similar ΔEab, ΔE00, and ΔWID across QC groups. The HP group showed greater reductions in hardness and increased roughness compared to others (p < 0.0001), while the HP/1%QC group resulted in no statistically significant alterations under the tested conditions. H2O2 diffusion was significantly greater in the HP group, while it was notably lower in the HP/1%QC group (p < 0.05). The incorporation of 1% quercetin into a 35% H2O2 gel maintains its bleaching efficacy while protecting enamel properties and reducing hydrogen peroxide diffusion. Quercetin-enriched H2O2 gels may enhance bleaching safety by protecting dental tissues while maintaining esthetic benefits.